The Relationship Between Mental Workload and Length of Service with Occupational Stress Among Health Center Employees in Pucung, Tulungagung - Nauroh Nadzifah, Helvy (Journal of Nutrition and Public Health, 2025)
Background: Occupational stress is a critical issue in healthcare, particularly in community health centers where the workload remains high even after the COVID-19 pandemic. The dual responsibility of administrative duties and patient care exposes employees to persistent mental strain, potentially affecting service quality. Aims: This study aims to examine the relationship between mental workload and length of service with occupational stress among employees of the Pucung Health Center in Tulungagung. Methods: A cross-sectional quantitative design was applied, involving 44 respondents selected randomly from a population of 50. Mental workload was measured using the NASA-TLX questionnaire, while stress levels were assessed using the HSE Questionnaire. Data were analyzed using Chi-Square tests and logistic regression, with significance determined at p < 0.05. Results: Most respondents reported moderate to high mental workload, and stress levels ranged from moderate to very high. Statistical tests revealed a significant relationship between both mental workload and length of service with occupational stress (p < 0.05). Logistic regression showed that high mental workload increased the risk of stress by 5.65 times, and long service tenure by 3.17 times. Conclusion: The findings confirm that mental workload and length of service significantly affect occupational stress among health center workers. These variables interact dynamically: newer employees struggle with adaptation, while senior staff face burnout. Therefore, health centers must adopt proactive strategies, including balanced task allocation, stress management training, and tenure-sensitive HR policies. Regular assessments using validated instruments like NASA-TLX and HSE Questionnaire should inform institutional responses. Implementing structured support systems will not only safeguard employee well-being but also enhance healthcare service delivery and institutional sustainability. Future policies should be tailored to workforce dynamics to reduce stress and foster a healthier work environment.